Tuning electricity generation throughout the year with PV module technology. (November 2020) - Manganiello, Patrizio; Govaerts, Jonathan; Horvath, Imre T.; Chowdhury, Mohammed Gofran; Yordanov, Georgi H.; Goverde, Hans; Aldalali, Bader; Beausoleil-Morrison, Ian; Valkealahti, Seppo; Lappalainen, Kari; Poortmans, Jef
Abstract: Currently, photovoltaic (PV) installations target a maximization of annual energy yield. However, as the grid penetration of PV is increasing, PV electricity generation will need to match better with local load profiles. Especially the seasonal variabilities remain challenging. While wind and PV tend to have complementary seasonal variability, wind turbine installation faces limitations especially in densely populated areas. In this paper, we discuss how this challenge may be addressed with climate- and consumption-specific PV module technology. In particular, we demonstrate how the temperature coefficient of a PV system can impact the energy yield throughout the year. In colder climates, higher temperature coefficients allow for a better energy balance, favoring production in colder seasons without a significant reduction of yearly energy yield. Simulations for locations at high latitude, and colder climates, indicate that higher temperature coefficients and improved low-light behavior not only enable a higher energy yield in cold seasons, but also negligible losses in the overall yearly energy yield compared to lower temperature coefficients and slightly better low-light behavior. Simulations show that these results can be obtained using commercial PV modules. More broadly, they indicate how PV module technology may be optimized depending on the location and climate. Highlights: Detailed energy yield simulations are carried out for 4 locations and climates. A high temperature coefficient may improve seasonal production in cold climates. Yearly energy yield is not necessarily sacrificed, even for commercial modules. Next to temperature coefficients, also low-light behaviour is important. Climate-specific modules could be considered for future grid-friendly PV systems.